GEOCHEMICAL ANALYSIS AND BASIN MODELING IN WEST MADURA OFFSHORE BLOCK, NORTH EAST JAVA BASIN - Pratama, Hengky
Geochemical analysis and basin modeling are important analyzes that have to do at the oil and gas exploration stage, by carrying out these two analyzes will clarify the existing petroleum system in a basin. The research was conducted on oil and gas fields located in the Offshore Block of West Madura, North East Java Basin. This area is one of the basins that produces good hydrocarbon production, but in the last few years the hydrocarbon production was declined and the new hydrocarbon producing fields have been not found yet in this area. Geochemical analysis and basin modeling are expected to increase opportunities for new field discoveries, so that hydrocarbon production can be increased. This research was begun with conducting analysis of source rock evaluation which consist of source rock richness analysis, determination of kerogen type, and level of maturity analysis. TOC analysis (Total Organic Carbon) is useful for determining the level of richness of the source rock. The determination of kerogen type is obtained by analyzing the result of rock pyrolysis. Vitrinite reflection data (Ro) is the main parameter that used in the maturity level of the source rock analysis. Biomarker analysis was also carried out in this research, this analysis serves to determine the origin of organic matter, depositional environment, level of maturity, and correlation between crude oil and source rock. Furthermore, this research is continued with basin modeling. It begins with 1D basin modeling than analyzed with 3D basin modeling. Generally, the basin model aims to determine history of source rock maturity, time of source rock maturity, time of hydrocarbon migration, and pathway of hydrocarbon migration. The evaluation of source rock was conducted in Ngimbang Formation and Kujung Unit II Formation. Ngimbang Formation have 0,51-3,56 % of TOC value (fair-very good), composed by type III of kerogen, and showing immature to peak mature maturity (0,49-0,76 % Ro). Kujung Unit II Formation have 0,5-2,2 % of TOC value (fair-very good), composed by type III of kerogen, and showing immature maturity (0,39-0,59 % Ro). Biomarker analysis of source rocks from Ngimbang Formation and Kujung Unit II Formation shows organic matter were derived from the mixture of higher plants and algae deposited in fluviodeltaic environment. Biomarkers analysis of crude oil shows that sample were from source rocks with organic matter derived from bacteria deposited in fluviodeltaic environment. Biomarker analysis in crude oil is vi also useful for determining the level of maturity, and the result shows that sample has maturity level 0,86-1,06 % Ro. Crude oil and source rocks from Ngimbang Formation and Kujung Unit II Formation have negative correlation. The 1 dimension basin modeling shows that there are two trends of source rocks maturity, trends in the paleo high and paleo low area. In paleo high area, source rocks maturity of Ngimbang Formation has entered peak mature and source rock of the Kujung Unit II Formation is still immature. In paleo low area, source rocks maturity of Ngimbang Formation also has entered peak mature and sorce rock of the Kujung Unit II Formation is still immature. Source rocks in paleo high area generate oil window on 0,36 Ma (Pleistocene) and reach peak mature phase on 0,1 Ma (Pleistocene). Source rocks in paleo low area start early mature stage on 26,72 Ma (Oligocene) and reach peak mature on 24,92 Ma (Oligocene). The hydrocarbon migration in 3 dimension basin modeling shows that the oil biomarker analysed does not come from the source rock in the study area. The crude oil is projected to come from a more deeper basin area, the east side of the study area.